Teaching a foreign language at technical university according to the blended learning model in LMS «English Patient» - Anastasia G. Shirokolobova; Georgii V. Shirokolobov (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The purpose of the work is to create a methodology for managing educational activities in LMS English Patient using blended learning model Flipped Classroom in the course of improving the language skills of university teachers. The study was conducted in four stages. At the first stage, the features and technical characteristics of the LMS English Patient for teaching foreign languages at the university were studied. At the second stage, the authors electronic course Professional English Language Development (PELD) was developed in LMS English Patient for teaching foreign languages at the university according to the model of blended learning Flipped Classroom. At the third stage, the methodology of organizing educational activities according to the Flipped Classroom model using the LMS English Patient is described. At the fourth stage, the level of formation of language skills while working in the LMS English patient was revealed.